205 Atrial Arrhythmia Susceptibility in Arrhythmogenic Right Ventricular Cardiomyopathy. (31st May 2014) - Syeda, Fahima; Kemper, Marcel; Vloumidi, Eleni; Holmes, Andrew; Osborne, Benjamin; Hopkins, Sarah; Yu, Ting; Riley, Genna; Kirchhof, Paulus; Fabritz, Larissa
Abstract : Background: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited disorder that causes sudden death and right ventricular heart failure in young athletes. Loss-of-function mutations in desmosomal proteins including plakoglobin deficiency are linked with ARVC and ventricular arrhythmias in trained mice. Chronic intensive endurance training increases susceptibility to atrial arrhythmias in rats. We tested whether heterozygous plakoglobin deficient (Plako+/-) mice that undergo moderate endurance training show increased atrial arrhythmia susceptibility compared to their wild type (WT) littermates. Methods: Plako+/- and WT mice were group swim-trained for 6 d/week, gradually increased to 90 min/d, with a total average swimming times of 50h over 8 weeks. Echocardiography was carried out before and after the swim-training period. Hearts were rapidly excised and immediately perfused with Krebs-Henseleit solution and left atrial (LA) monophasic action potentials (MAPs) were recorded. Inter-atrial activation times (AT) and action potential durations (APDs) were measured during RA pacing at 100 ms fixed-rate cycle lengths. An 8-pulse S1 train, at 100 ms cycle length (CL), followed by a single extrastimulus, S2, was delivered to assess atrial arrhythmia inducibility (arrhythmias >1s). AT and APD90 values are expressed as mean ±SEM. Transmembrane action potentials (TAPs) from sedentary mice were recorded from isolated, superfused LA using floating glass microelectrodes at 100 ms paced CL. APD was measured as the average of 8 consecutive APs. AT and APD90 values are expressed as mean ±SEM. Results: The number of hearts with atrial arrhythmias was greater in swim-trained Plako +/- (6/13 hearts, )than swim-trained WT (0/8 hearts) Hearts of trained Plako +/- mice were more susceptible to induced ventricular arrhythmias than trained WT mice (WT: 1/12; Plako +/- : 7/15 hearts, p < 0.05). Training increased left ventricular wall width by 13% in both WT and Plako +/- mice (WT: 0.58 ± 0.01 baseline vs. 0.66 ± 0.01 mm trained; Plako +/- : 0.58 ± 0.02 baseline vs. 0.66 ± 0.01 mm trained). Right ventricular size was increased in trained Plako +/- vs. trained WT, e.g. RV diameter measured parasternally was increased in Plako +/- (1.77 ± 0.03 mm) vs. WT (1.51 ± 0.03 mm) after training, p < 0.05. Atrial weight was unchanged between genotypes. Intra-atrial AT in sedentary mice measured using MAPs and TAPs were the same in both genotypes. Inter-atrial AT between the RA endocardial pacing site and the LA MAP electrode in trained mice also did not differ between genotypes. LA APD90 measured from MAPs in trained mice and MAPs and TAPs from sedentary mice, TAP amplitude, and TAP maximum upstroke velocity were unaffected by genotype. Thus far, we have not observed increased arrhythmia inducibility in sedentary Plako +/- mice. Conclusion: Our observations suggest that defective mechanical cell-cell contact proteins predispose to moderate training-induced atrial arrhythmias.